Legal regulation of football – prohibitions and limitations - Nikolova, Raina (Law Journal of New Bulgarian University, 2021)
In the article under discussion is the administrative regulation of sports organizations and professional football clubs in Bulgaria. It analyses the legal regulation of sports hooliganism. Also presented are the types of measures and administrative penalties imposed as a result of sports bullying.